2014
DOI: 10.1093/annonc/mdu288
|View full text |Cite
|
Sign up to set email alerts
|

Plasma circulating tumor DNA as an alternative to metastatic biopsies for mutational analysis in breast cancer

Abstract: Plasma can be prospectively tested as an alternative to metastatic biopsies in molecular screening programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
144
2
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 216 publications
(154 citation statements)
references
References 20 publications
5
144
2
3
Order By: Relevance
“…Roth e and colleagues found a sensitivity of cfDNA estimated at 82% in 11 patients with mutated metastatic breast cancer (27). Another study found a sensitivity rate of 58% in 50 mutated metastatic lung cancer patients (28).…”
Section: Discussionmentioning
confidence: 98%
“…Roth e and colleagues found a sensitivity of cfDNA estimated at 82% in 11 patients with mutated metastatic breast cancer (27). Another study found a sensitivity rate of 58% in 50 mutated metastatic lung cancer patients (28).…”
Section: Discussionmentioning
confidence: 98%
“…17 The use of dPCR for ctDNA analysis has been reported previously for MBC, but only after deep sequencing of the primary tumor to define the non-recurrent driver mutations of TP53, PI3KCA or PTEN. 13,17,20,21 For ESR1, few activating mutations confined to codons 537 and 538 in exon 8 represent 74% of the described mutations, limiting the number of contributing designs 8 and the requirement for sequencing metastases. A more complex and non-invasive method for the determination of the ESR1 mutational status using a culture of circulating tumor cells has been described previously.…”
Section: Short Reportmentioning
confidence: 99%
“…Rothé et al described that known mutations can be detected in the blood using a targeted NGS approach when a coverage of 25,000x is used. 56 Since the isolation of CTCs is more challenging than the isolation of ctDNA, clinical studies are ongoing to test whether CTCs can be used for monitoring treatment response. 56,57 In conclusion, liquid biopsies seem a reliable, non-invasive method to detect low-level molecular alterations for the follow-up of cancer treatment.…”
Section: Liquid Biopsymentioning
confidence: 99%